(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The emergence of online social networksinfluences people in various ways and moreover, the effect is predicted to behigh on the young adolescents wherein we find that target group who is moreexposed themselves to the online social media. It is believed that the socialnetworks such as online brand communities influence the purchase intentions andin turn enhances brand trust and loyalty. Taking the perspective of the brandcommunity building plus the brand trust and loyalty literatures, our goal is toshow how brand communities based on social media influence elements of thecustomer centric model (i.e., the relationships among focal customer and brand,product, company, and other customers) and brand loyalty.